Autonomy in Indonesian Counseling Students at Universities: A Comparative Study - Yuca, Verlanda; Suherman, Uman; Nurihsan, Juntika; Budiman, Nandang; Magistarina, Elrisfa (KONSELOR, 2025)
Student autonomy refers to an individual's ability to manage their own learning process, make informed academic decisions, and take responsibility for their personal development. The level of autonomy can vary depending on the campus environment, learning approach, and the type of academic support provided. This study aims to describe and analyze the differences in student autonomy between Universitas Negeri Padang (UNP) and Universitas Pendidikan Indonesia (UPI). This study used a comparative, descriptive, and quantitative approach. Samples were purposively selected from students at Universitas Negeri Padang and Universitas Pendidikan Indonesia who actively attended lectures. The data collection instrument was The Autonomy Questionnaire for Students with the Guttman scale model with "yes-no" formats as answer choices that measured the dimensions of learning autonomy, decision-making, and academic responsibility. Data were analyzed using descriptive statistics and a comparative test (t-test). The results of the analysis showed that Universitas Pendidikan Indonesia students had a higher level of autonomy than students from Universitas Negeri Padang. Most respondents from Universitas Pendidikan Indonesia were in the high autonomy category, while 50.4% of respondents from Universitas Negeri Padang were in the moderate category. The t-test results revealed significant differences between the two groups of students in aspects of decision-making and independent learning management. These differences can be attributed to variations in learning approaches, the role of lecturers as facilitators, and the more supportive academic environment at Universitas Pendidikan Indonesia. The results of this study emphasize the importance of developing learning strategies and campus culture that can encourage student autonomy more evenly across universities.